Case Study on the Employment of a Person with Intellectual Disability in Childcare Work in Japan - Maebara, Kazuaki (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: In recent years, it has become necessary to promote the employment of persons with intellectual disabilities in new occupations. Objective: This study aimed to analyze the case of a person with an intellectual disability employed in childcare work and examine it from the perspective of issues in securing employment for the disabled. Method: As a case study, an in-depth interview was conducted to survey a director of the Center for Early Childhood Education and Care, which had been hiring persons with intellectual disabilities and organizing the employment process for about four years. Results: The person with intellectual disability was assigned to perform direct support work, mainly childcare work, and was aided by staff members responsible for guidance and the verbalization of job instructions. In addition, the staff provided specific guidance for solving problems that occurred in daily life. The work could be carried out smoothly. Conclusion: While many people with intellectual disabilities are engaged in indirect support work, participating in direct support work, mainly childcare work, may positively affect their career development. Additionally, in focusing on the workplace, it is important to reconsider daily life issues from the viewpoint of long-term stability in the workplace and improve the methods used for transition support. The data were collected from a single case, which may limit the generalisability of the findings.